A fala de Maria no Magnificat aos povos do terceiro milênio – Para uma mística evangélica (I) - Boff, Lina (Revista eclesiástica brasileira, 2000)
The authoress reflects upon the Magnificat from the point of view of the poor masses and the mass of excluded people from the established system. She attributes to the former the phrases of the verses of the Song of Mary that manifest a larger taking on of consciousness and, for this reason, are the most prophetic and evangelically courageous phrases which Mary proclaims. The phrases of the Song in which Mary speaks with caring and tenderness are designated towards the mass of excluded people for whom there is nothing left except life itself and the oxygen they breathe. For these people just revindications cannot be hoped for nor the consciousness which brings about such justice, since for them it is sufficient to have life and nothing more. Confrontation with those stronger would clearly signal death. Mary addresses those excluded as the Mother of Life and the Mother Protectress of this Life. The authoress concludes saying that, from this point of reflection, a fight for the concrete values of the Kingdom and a contemplation which knows how to be silent should erupt, without closing one’s eyes to the reality that God the Father-Son-Holy Spirit reproves and in the middle of which He gives rise to prophets and prophetesses to defend, above all, the excluded parte of His People.